“Treat them as a human being”: dignity in police detention and its implications for ‘good’ police custody - Skinns, Layla (The British journal of criminology, 2020)
Here, we examine the factors influencing whether those detained by the police feel treated with dignity. We develop a human rights-oriented conception of dignity rooted in the equal worth of human beings, encapsulated in detainees’ desire to be ‘treated like a human being’. The predictors of this are examined using multilevel modelling of survey data collected from 371 detainees in 27 custody facilities in 13 police forces in England and Wales in an Economic and Social Research Council-funded study of ‘good’ police custody. We found that perceptions of the material conditions predicted feelings of dignity, as did detainees’ reactions to being detained, their perceptions of the culture of police custody and the mechanisms used to hold the police to account. Feelings of dignity were also less likely for younger adults and for Black Asian and Minority Ethnic detainees, with these experiences being mediated by less trust in accountability mechanisms. This paper concludes by examining the implications for ‘good’ police custody.